Electrospinning Trilayer Dressing of PLA/ZnO with Controlled Released Profiles for Visible pH Monitoring and Effective Exudate Management - Zhang, Jun (Langmuir : the ACS journal of surfaces and colloids, 2025)
To address persistent challenges in wound care, including exudate management, infection prevention, and healing monitoring, this study developed a multifunctional fiber dressing using electrospinning technology. The system integrates a patterned hydrophobic polylactic acid/zinc oxide (PLA/ZnO) inner layer providing antimicrobial protection and exudate drainage; a polyacrylonitrile/polydopamine (PAN/PDA) intermediate water transport layer enabling unidirectional exudate transfer; and an outer PAN-based functional membrane incorporating sodium polyacrylate (SPA), phenol red (PSP), and tetracycline hydrochloride (TCH) for controlled drug release and visual wound status monitoring. The comprehensive evaluation revealed exceptional performance: rapid exudate removal within 3.35 s, 96 h sustained antibacterial drug release (68.6% cumulative release), pH-responsive chromatic transition (yellow-to-red at pH 5-9), and significant antimicrobial efficacy against Escherichia coli and Staphylococcus aureus (inhibition zone diameters of 10 and 18 mm, respectively). The dressing exhibited a balance of mechanical strength (6.1 MPa tensile strength) and breathability (13.4 mm/s air permeability rate). By integrating three core functions─efficient exudate management, antimicrobial regulation, and intelligent healing monitoring─this multifunctional architecture demonstrates clinical applicability in postoperative care and chronic wound therapy